Coordination failure in capacity-then-price-setting games - Werner Güth; Manfred Stadler; Alexandra Zaby (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
In capacity-then-price-setting games, soft capacity constraints are planned sales amounts where producing above capacity is possible but more costly. While the subgame perfect equilibrium predicts equal prices, experimental evidence often reveals price discrepancies. This failure to coordinate on equal prices can imply losses, especially when serving demand is obligatory. We compare coordination failure with efficient rationing as well as with compulsory serving of demand, and additionally allow for simultaneous and sequential capacity choices. These treatments lead to a varying severity of the threat of losses. Our experimental results show that (possible) coordination failure affects behavior through two channels: via anticipating as well as via reacting to a loss. While capacities increase in anticipation of losses, prices increase when anticipating losses but decrease after experiencing losses. Coordination failures are more probable after subjects experienced a loss.
urn:nbn:de:bsz:21-dspace-855837
Keywords: C72; C91; 330; capacity-then-price competition; loss avoidance; path dependence; sequentiality of decisions; intra-play communication